Understanding the adsorptive interactions of carbon dioxide with metal-organic framework (IRMOF-1) using a theoretical approach - Thi Thao, Ha; Thi Lan, Phung; Dinh Thoai, Nguyen; Thanh Hue, Tran; Ngoc Ha, Nguyen; Ha, Nguyen Thi Thu (Vietnam Journal of Science and Technology, 2022)
Density Functionalbased Tight-binding method with dispersion corrections and Molecular Dynamics (MD) simulations were performed to study the carbon dioxide (CO2) adsorption process on a metal-organic framework (IRMOF-1). The adsorption centers, adsorption energy, adsorption capacity, diffusion coefficient, and the effect of temperature on the adsorption process have been thoroughly examined and elucidated.The calculated results reveal that the favorable CO2adsorption site on IRMOF-1 is the position where the CO2molecule is located in the cavity formed by themetalclusterand oxygenatoms of the three –COO groups of the organicligand. The CO2moleculeswereinstantly adsorbed on the IRMOF-1structure as "anchors" to hold the next molecules in place. The Monte Carlo simulation results demonstrate that when the concentration of CO2molecules is low, they preferentially adsorb onto the surface of IRMOF-1. As the number of CO2molecules increases, they will gradually occupy the free space inside the crystal. The MD simulations with constant volume and temperature have shown that up to 350K, CO2was still dynamically adsorbed on IRMOF-1, without being desorbed.The calculated diffusion coefficients implythat CO2would diffuse into IRMOF-1 slower thanmethane, but quicker than oxygen and nitrogen. Therefore, it is feasible to separate CO2from itsmixturewith oxygen and nitrogen using IRMOF-1.